Preservation of Bima Language Vocabulary in the Bima Community Who Live in Mataram - Adhar, Yusuf Idin (Jurnal Ilmiah Mandala Education (JIME), 2024)
Language is not just a means of communication in the relationship between mother and child, but rather reflects the emotional closeness between the two. More than that, language forms a person's character, even as a vehicle for addressing spiritual values for society. This research uses qualitative descriptive research. Data collection methods are observation, interviews and recording. How to determine informants in this research uses an approach snowball sampling Where the technique for determining data sources is that if the number of informants can meet the objectives, then the data is considered valid. The data analysis technique in this research is qualitative descriptive analysis technique. The results of this research show that the Bima language in the Bima community who live in Mataram is able to survive, even though the Bima language is in the midst of the Sasak tribe community which uses Sasak language as the majority language.